SYSTEMATIC ANALYSIS AND SPECIES DIVERSITY OF PHYTONEMATODES INCLUDING POTATO ROOTS AND ITS SURROUNDING SOILS (Scientific journal of the Fergana State University, 2025)
The article presents data on the systematic analysis of nematodes found in potato plants grown in the farms of Mingbulok district of Namangan region. As a result of the research, 139 nematodes belonging to 19 species were recorded in potatoes and their root zone soil. The identified phytonematodes belong to 1 subclass - Secernentea, 3 orders - Dorylaimida, Rhabditida, Tylenchida, 7 families Panagrolaimidae, Cephalobidae, Aphelenchidae, Aphelenchoididae, Tylenchidae, Hoplolaimidae, Angunidae and 14 genera. Of the nematode species identified in plant organs and root zone soil, 4 are dominant, 12 are subdominant, 2 are recidivist, and 2 are subrecidivist.